Cancer metastasis: Mechanisms of inhibition by melatonin. Issue 1 (25th November 2016) - Su, Shih‐Chi; Hsieh, Ming‐Ju; Yang, Wei‐En; Chung, Wen‐Hung; Reiter, Russel J.; Yang, Shun‐Fa
Abstract: Melatonin is a naturally occurring molecule secreted by the pineal gland and known as a gatekeeper of circadian clocks. Mounting evidence indicates that melatonin, employing multiple and interrelated mechanisms, exhibits a variety of oncostatic properties in a myriad of tumors during different stages of their progression. Tumor metastasis, which commonly occurs at the late stage, is responsible for the majority of cancer deaths; metastases lead to the development of secondary tumors distant from a primary site. In reference to melatonin, the vast majority of investigations have focused on tumor development and progression at the primary site. Recently, however, interest has shifted toward the role of melatonin on tumor metastases. In this review, we highlight current advances in understanding the molecular mechanisms by which melatonin counteracts tumor metastases, including experimental and clinical observations; emphasis is placed on the impact of both cancer and non‐neoplastic cells within the tumor microenvironment. Due to the broad range of melatonin's actions, the mechanisms underlying its ability to interfere with metastases are numerous. These include modulation of cell–cell and cell–matrix interaction, extracellular matrix remodeling by matrix metalloproteinases, cytoskeleton reorganization, epithelial–mesenchymal transition, and angiogenesis. The evidence discussed herein will serve as a solid foundation for urging basic and clinical studies on the use of melatonin to understand and control metastatic diseases.